Mobile Counselling Online an Alternative Counselling Guidance System for Millennial Era Student - Fahyuni, Eni Fariyatul; Taurusta, Cindy; Hariastuti, Retno Tri; Bandono, Adi; Muhid, Abdul (Journal of Education Technology, 2021)
During the COVID-19 pandemic, there is a shortage of counseling guidance services, so students have difficulty consulting with teachers. This study aims to analyze the counseling service system during the COVID-19 pandemic on the introduction of potential and preparation of learning strategies for middle and high school students in the Sidoarjo district. This research design is a mixed-method with quantitative and qualitative approaches using exploratory factor analysis, and further research and development (R&D) is carried out to produce products in the form of online counseling guidance services. The qualitative exploratory factor analysis results revealed various problems experienced and needed by students during the COVID-19 pandemic. Quantitatively showing eight forms of guidance and counseling services, strengthening skills with the highest score of 0.999 affected increasing self-efficacy and achievement motivation. The findings of this study indicate that online counseling services are very much needed to recognize potential and problems. The online counseling guidance service developed must meet three factors: understanding the potential for effective learning, developing and developing learning strategies, and building internal and external motivation. The innovation of online counseling guidance services must consider the factors of convenience, convenience, and user confidentiality that are adaptive, flexible, and unlimited in the millennial era.